Blood-triggered self-sealing and tissue adhesive hemostatic nanofabric - Yan Fang; Linyu Wang; Xinwei Zheng; Peng Ni; Zhibo Xu; Ziying Wang; Yunxiang Weng; Qinhui Chen; Haiqing Liu (Nature Communications)
Abstract Current hemostatic fabric often encounters the issue of blood seeping or leaking through the fabric and at the junctions between the fabric and tissue, leading to extra blood loss. Herein, we report a hemostatic nanofabric composed of anionic and cationic nanofibers. Upon contact with wound, the porous nanofabric can absorb the interfacial blood and self-seal to form a compact physical barrier through interfiber bonding, preventing blood from longitudinally penetrating the fabric. This process results in the encapsulation of blood components within the electrostatically crosslinked nanofiber network, creating a robust thrombus that reinforces the physical barrier. Moreover, this nanofabric exhibits strong tissue adhesiveness, inhibiting blood seeping out at the seam of the fabric and tissue. Its hemostatic performance in animal injuries surpasses that of standard cotton gauze and Combat GauzeTM. In the pig femoral artery injury, the blood loss from the nanofabric is only ca. 8% of that from Combat GauzeTM. The nanofabric exhibits excellent biodegradability, hemocompatibility, cytocompatibility, antibacterial activity, and wound healing promotion.